(untitled) (Eurasian Scientific Herald, 2023)
The aim of the present paper is to demonstrate translation of number component phraseological units from English into Uzbek language in view of form and meaning. Phraseological units, proverbs and sayings react to all phenomena of reality, reflect the life and worldview of the people in all its diversity, they convey every day, social, philosophical, religious, moral, ethical, and aesthetic views of the people. Also, with this task proverbs cope very successfully. Their subject matter is truly limitless. They cover absolutely all aspects of human life, the most diverse relationships between different phenomena of reality.